The five‐items memory screen‐extended variant: A tool for assessing memory. (19th November 2019) - Balogh, Nora; Åstrand, Ragnar; Wallin, Anders; Rolstad, Sindre
Abstract : Background and purpose: The detection of memory impairment is an important part of dementia screening. However, the scope of memory measures in current screening batteries is limited. There is a need for a short yet sensitive instrument for early detection of memory impairment that could serve as a complement to existing globally oriented screening tests, for example, Mini‐Mental State Examination (MMSE). To that end, the current study investigates the sensitivity and psychometric properties of the memory screening instrument The Five‐Items Memory Screen ‐Extended Variant (FIMS‐XV). Methods: Hundred and forty‐five participants included in the Gothenburg Mild Cognitive Impairment Study—27 patients with subjective cognitive impairment (SCI), 73 with mild cognitive impairment (MCI), and 45 with mild dementia—underwent cognitive screening including the MMSE and FIMS‐XV. Ninety participants also underwent extensive neuropsychological testing. Results: The FIMS‐XV showed high internal consistency and strong correlations with established neuropsychological memory tests. Both the FIMS‐XVdelayed recall score and the FIMS‐XV total score differentiated mild dementia patients from patients with SCI and MCI. Conclusions: The FIMS‐XV shows promise as a sensitive tool for screening for memory impairment in all putative phases of dementia.